2013
DOI: 10.1093/jjco/hys231
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab Treatment for Symptomatic Radiation Necrosis Diagnosed by Amino Acid PET

Abstract: Bevacizumab is effective in treating radiation necrosis; however, radiation necrosis was not definitively diagnosed in most previous reports. Here we used amino acid positron emission tomography to diagnose radiation necrosis for the application of bevacizumab in treating progressive radiation necrosis. Lesion/normal tissue ratios of ,2.5 on 18 fluoride-labeled boronophenylalanine-positron emission tomography were defined as an indication of effective bevacizumab treatment. Thirteen patients were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 12 publications
1
65
0
Order By: Relevance
“…Since vascular endothelial growth factor (VEGF) is also a vascular permeability factor in the brain, 1 bevacizumab, a humanized antibody that inhibits VEGF, would be expected to reduce perilesional edema that often accompanies BRN. 26 However, bevacizumab's optimal dose, dosing interval, and duration of efficacy have not been fully defined.…”
mentioning
confidence: 99%
“…Since vascular endothelial growth factor (VEGF) is also a vascular permeability factor in the brain, 1 bevacizumab, a humanized antibody that inhibits VEGF, would be expected to reduce perilesional edema that often accompanies BRN. 26 However, bevacizumab's optimal dose, dosing interval, and duration of efficacy have not been fully defined.…”
mentioning
confidence: 99%
“…However, bevacizumab is an anti-angiogenic drug recognized for its role in pruning vessels and promoting blood supply, which is inconsistent with the above inference [25]. We believe that several mechanisms are [26].Among many previous studies, only a few have reported several recurrence cases [4][5][6][7][8][9][10]. Our literature review shows that previous researchers may have missed progression in many cases reported as "without progression" due to individual differences in bevacizumab sensitivity, short follow-up times after bevacizumab is discontinued, or death shortly after bevacizumab is discontinued.…”
Section: Discussionmentioning
confidence: 70%
“…Compared to previous reports, most studies [4][5][6][7][8][9][10] only reported the efficacy of bevacizumab in the treatment of radiation-induced cerebral necrosis, while there were fewer studies on the recurrence and progression of radiation-induced cerebral necrosis after treatment. No studies have yet explored the reasons for recurrence and progression.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The use of bevacizumab has been reported to improve neurological symptoms and signal alterations in MRI of cerebral necrosis in adults and 4 children [1,8,9,10] treated for malignant tumors. A phase I trial with 14 patients suggested positive effects on cerebral radiation necrosis [1].…”
Section: Introductionmentioning
confidence: 99%